Primary and Metastatic Brain Tumours Assessed with the Brain and Torso [18F]FDG PET/CT Study Protocol-10 Years of Single-Institutional Experiences - Agata Pietrzak; Andrzej Marszałek; Tomasz Piotrowski; Adrianna Medak; Katarzyna Pietrasz; Julia Wojtowicz; Hubert Szweda; Krzysztof Matuszewski; Witold Cholewiński (MDPI AG, 2021)
According to the international societies' recommendations, the 2-deoxy-2-[18F]fluoro-D-glucose positron emission tomography/computed tomography ([18F]FDG PET/CT) technique should not be used as the method of choice in brain tumour diagnosis. Therefore, the brain region can be omitted during standard [18F]FDG PET/CT scanning. We performed comprehensive literature research and analysed results from 14,222 brain and torso [18F]FDG PET/CT studies collected in 2010-2020. We found 131 clinically silent primary and metastatic brain tumours and 24 benign lesions. We concluded that the brain and torso [18F]FDG PET/CT study provides valuable data that may support therapeutic management by detecting clinically silent primary and metastatic brain tumours.